2011
DOI: 10.1128/jcm.00849-11
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of a Catalase-Negative Staphylococcus aureus subsp. aureus Strain Collected from a Patient with Mitral Valve Endocarditis and Pericarditis Revealed a Novel Nonsense Mutation in the katA Gene

Abstract: We report a case of endocarditis and pericarditis caused by catalase-negative Staphylococcus aureus. Molecular characterization revealed a novel nonsense mutation in the katA gene, leading to a loss of 238 amino acids (47% of the wild-type catalase protein), including the heme-binding site, NADPH-binding region, and Tyr-337, essential for catalysis. CASE REPORTA 15-year-old boy presented to the Accident and Emergency Department with a 2-day history of fever, rhinorrhea, vomiting, and colicky abdominal pain. Hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
11
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 24 publications
1
11
0
Order By: Relevance
“…In this study, we detected a nonsense mutation at position C1180T, which caused a codon change from CAA to TAA (stop codon). We therefore hypothesize that a single codon mutation is responsible for the loss of catalase activity in this bacterium, similar to what has been previously described (21). Sequence analysis showed that the N-terminal arm of the catalase gene in our isolate was conserved, whereas the rest of the gene was either disrupted or lost due to the premature termination of the translation process.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…In this study, we detected a nonsense mutation at position C1180T, which caused a codon change from CAA to TAA (stop codon). We therefore hypothesize that a single codon mutation is responsible for the loss of catalase activity in this bacterium, similar to what has been previously described (21). Sequence analysis showed that the N-terminal arm of the catalase gene in our isolate was conserved, whereas the rest of the gene was either disrupted or lost due to the premature termination of the translation process.…”
supporting
confidence: 87%
“…Grüner et al reported a frameshift mutation due to a 5-base deletion upstream of the initiation codon of the catalase gene (16), whereas a T172C substitution, leading to a histidine 58-to-tyrosine change, and a G636A substitution, leading to an arginine 212-to histidine change, have been reported by Piau et al (11). To et al (21) identified 15 silent mutations; a critical nonsense mutation at position 802, leading to a change from codon GAA to TAA (stop codon); and 4 additional mutations downstream of the nonsense mutation. In this study, we detected a nonsense mutation at position C1180T, which caused a codon change from CAA to TAA (stop codon).…”
mentioning
confidence: 96%
“…Some researchers have observed a correlation between virulence and catalase activity (8,22,23), and yet others have not found any evidence of such a correlation (24,25). Nevertheless, clinical isolates of catalase-negative S. aureus appear to have a role in human infections (11)(12)(13)(14)(15)26). Clonal outbreaks of catalase-negative S. aureus infections have been reported, suggesting that such strains are as virulent as wild-type strains (27,28).…”
mentioning
confidence: 99%
“…While infections caused by catalase-negative S. aureus have been reported, these reports are rare. Furthermore, few studies have used robust molecular testing to definitively identify the organism or to determine the mutation responsible for catalase deficiency (7)(8)(9). Therefore, we sought to further characterize the catalase-negative infecting strain.…”
mentioning
confidence: 99%